Leo + Lea - Wesolowska, Monica, 1965- (Scholastic Press, 2022)
Leo is totally fixated on numbers and counting everything, even the words in the story the teacher reads; Lea is the shy new girl who shares his desk, and spends all her time drawing--but one day, in the noise of the playground, an accident brings them and their obsessions together in the beginning of a friendship.